Genomic characteristics of a novel reovirus from Muscovy duckling in China - Yun, Tao; Yu, Bin; Ni, Zheng; Ye, Weicheng; Chen, Liu; Hua, Jionggang; Zhang, Cun (Veterinary microbiology, 2014)
A new reovirus was isolated from a sick Muscovy duckling with hemorrhagic-necrotic lesions in the liver in Zhejiang, China in 2000 and was tentatively denoted a new type of Muscovy duck reovirus (N-MDRV ZJ00M). This reovirus was propagated in a chicken fibroblast cell line (DF-1) with obvious cytopathic effects. The reovirus's genome was 23,419bp in length with an approximately 50% G+C content and 10 dsRNA segments encoding 12 proteins. The length of the genomic segments was similar to those of avian reoviruses (ARVs), which range from 3959 nt (L1) to 1191 nt (S4) in size. All of the segments have the conserved terminal sequences 5′-GCUUUUU…UUCAUC-3′, and all of the genome segments, with the exception of S1, apparently encoded one single primary translation product. The genome analysis revealed that the S1 segment of N-MDRV is a tricistronic gene that encodes the overlapping ORFs for p10, p18, and σC. This finding is similar to that found for ARVs but distinct from that found for classical MDRV and GRV, which have a bicistronic S4 segment that encodes p10 and σC and do not encode p18. The amino acid (aa) alignments of the putative proteins encoded by the main ORF in each segment revealed a high similarity (14.1–100%) to the counterpart proteins encoded by other ARV species from the avian orthoreoviruses (e.g., ARV, classical MDRV and N-MDRV) in the Orthoreovirus genus, particularly with N-MDRV (94.6–100%). The phylogenetic analysis of the nucleotide sequences of all 10 genome segments revealed that N-MDRV ZJ00M is distinct from all other described reovirus species groups but is a separated from the ARV (including MDRV and GRV) species within orthoreovirus species group II and grouped into the classical MDRV and GRV genogroup with the N-MDRV isolates. The MDRV genogroup can be further divided into two genotype clusters. The morphological and pathological analyses and the genetic characterization of N-MDRV ZJ00M suggest that it belongs to genotype 2 (N-MDRV). In addition, the RT-PCR assays of DRV diseased duckling and gosling samples collected from different regions of China during 2000–2013 indicate that N-MDRV is currently the prevalent genotype in China.